A molecular dynamics study of Al³⁺ in water: hydrolysis effects - Druchok, M.; Holovko, M.; Bryk, T. (Condensed Matter Physics, 2004)
A molecular dynamics study of Al³⁺ in water was performed. A flexible non-constrained central force model for water molecules was used. This permitted one to take into account a tendency of cation hydrolysis effects. We observed strict octahedral arrangement of neighbours in aluminium cation hydration shell, two of six neighbours being water molecules, the rest four being OH⁻ groups that appeared as a consequence of cation hydrolysis. Four created protons leave the first hydration shell and transfer to the second one. Those protons are strongly bonded to cation hydration shell, which implies that total charge of hydration shell does not change. Structural and dynamical features of the obtained hydration shell of Al³⁺ are reported. Нами було проведено моделювання водного розчину Al³⁺ методом молекулярної динаміки. Для опису води було використано нежорстку модель центральних сил, що дозволило описати ефекти гідролізу. Отримана гідратна оболонка алюмінію характеризується строгим октаедричним впорядкуванням найближчих сусідів: двох молекул води і чотирьох OH⁻ груп, утворених в результаті катіонного гідролізу. Чотири відірвані протони знаходяться в другій гідратній оболонці, залишаючись тісно зв’язаними з першою гідратною оболонкою, внаслідок чого повний заряд всього гідратного комплексу залишається незмінним. В статті представлено структурні і динамічні властивості гідратної оболонки іона Al³⁺.